A vida (e a morte) de Cláudio Manuel da Costa: poeta árcade, escravocrata e inconfidente (Almanack, 2022)
SOUZA, Laura de Mello e.Cláudio Manuel da Costa: o letrado dividido.São Paulo: Companhia das Letras, 2011. 242p.